(untitled) (Research, Society and Development, 2021)
Assessment of learning in higher education has been characterized as a fruitful subject in the Brazilian educational scenario, as it constitutes a complex and extremely relevant pedagogical process. This study purposes to reflect on the assessment of learning in higher education, aiming to understand and critically analyze this process and the questions that address the evaluative practices. Therefore, this work is based on scientific studies and research on the topic addressed. Results are presented and discussed based on bibliographic and documentary research that point out that although the assessment of learning in higher education is a necessary process, it is not an instrument of control, classification or coercion, but an instrument to investigate the level of learning of students. Consequently, we conclude that, the assessment cannot be dissociated from the teaching-learning process, given that it subsidizes information to the teacher, regarding the academic development, as well as information for the teacher to reflect and (re)think his own pedagogical practice. We also highlight the need for further debates on this subject, in view that the topic addressed needs to be much more discussed among education researchers, given the low production of scientific research on the subject articulated to Brazilian higher education.